'What to do over the week-end': Towards an understanding of distraction, advertising and newspaper coverage of the Kansas City jazz scene in the 1930s. (13th October 2019) - Bushard, Anthony
Abstract : In the 1930s, everyday Kansas Citians distracted themselves in numerous ways followingthe work week. But where did one turn to discover the best place to have a goodtime in the Midwest's vice capital? A major source was print media. Like most cities, several newspapers served 'Kaycee', notably the Kansas City Star and the Kansas CityJournal-Post. Relatedly, the Kansas City Call was an important social mechanism forAfrican Americans newly emigrated from the South. What one notices after examiningthese newspapers is: 1) nightclub advertisements bombard readers with vivid sensorydetails designed to promote a venue's opulence and 2) the portrayal of the entertainmentscene differs markedly depending on the source. Applying Ben Highmore's conceptof 'distraction' (Ordinary Lives, 2011), this article argues that 'distraction advertising'paradoxically unifies-through everyday dynamics like race, sexuality, class, and evenfood/drink-each newspaper's depiction of the 'Amusements' section while reinforcingtarget readership demographics.